Indebtedness and Subjective Financial Wellbeing of Households in Indonesia - Handayani, Dwini (Economics and Finance in Indonesia, 2016)
Indebtedness is an element to foresee household financial wellbeing. This vulnerability could be determined objectively and subjectively. Objective financial vulnerability is the objective ability to make ends meet that is analyzed using household income and characteristics. Measurement in subjective welbeing is determined by household perceptions in their ability to make ends meet. Household behavior with different perceptions will behave differently. Indebtedness is analyzed using the Indonesian Family Life Survey (IFLS) 5 with the Ordinary Least Square method. The inferential shows that both objective and subjective financial wellbeing influence household indebtedness. Kedalaman hutang merupakan elemen untuk mengetahui kesejahteraan finansial rumah tangga. Kerentanan ini dapat dilihat secara objektif maupun subjektif.